The Quality of Governance : 'Second-Generation' Civil Service Reform in Africa. (IMF Working Papers; Working Paper, 1998)
This paper argues that the development of human capital in the public sector should be an important ingredient in any proposed set of 'second-generation' reforms for Africa. In the post-colonial era the quality of governance has seriously declined, and the stock of human capital in the public sector has been eroded by a flight of human capital from many countries in response to compression of wages. The paper develops a simple theoretical framework to discuss these issues and the continent's experience with foreign technical assistance in supplementing the low level of domestic human capital.